Analysis of Gen Z's Green Investment Intention: The Application of Theory of Planned Behavior - Vidia Ratu Balqis Malzara; Umi Widyastuti; Agung Dharmawan Buchdadi (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
Green investment intentions have emerged in response to the challenges of climate change and the urgent need to adopt sustainable economic practices. The purpose of this study was to determine the factors that influence green investment intentions in Generation Z in Jakarta, with an age range between 17-26 years. This study used a purposive sampling technique with survey data collection methods. Data was collected using Google Forms with a total of 384 respondents. Data were analyzed using Structural Equation Model (SEM) through AMOS 24.0 software. The results showed that attitudes toward green investment had a significant effect on green investment intentions and perceived behavioral control had a significant effect on green investment intentions. In contrast, subjective norms had no significant effect on green investment intentions.